Clusters As a Driving Engine for FDI - Yehoue, Etienne (IMF Working Papers; Working Paper, 2005)
This paper develops a model that highlights the importance of clusters for attracting foreign direct investment. It shows from a game theoretical perspective how the combination of setting up a cluster and implementing policy reforms will be a key engine for attracting FDI. Based on agglomeration externalities, the paper shows that the very emergence of clusters can make investment so profitable that investors can even afford to tolerate more policyinduced distortions than otherwise. With perfect information, it shows the existence of multiple equilibria, in which some countries attract FDI while other do not. An extension to the context of imperfect information refines the analysis to a unique equilibrium, in which some investors respond to reforms. The paper presents case studies to support the findings.